Perspective of usage of PPARγ agonists melanin and pioglitazone under the prolonged gastric hypoacidity - Tsyryuk, O.I.; Beregova, T.V. (Ukrainian Antarctic Journal, 2015)
It was investigated the effects of agonists of nuclear receptors peroxisome proliferator-activated receptors gamma (PPARγ) melanin and pioglitazone оn the secretory function of the stomach in rats under long hypoacidity of gastric juices caused bу the introduction of Н+-К+- ATPase blocker omeprazole during 28 days. As а result of studies it was found that administration of omeprazole for 28 days leads to increase of hydrochloric acid secretion of stomach, resulting in the development of hypergastrinemia. Activation of PPARy Bу pioglitazone and melanin in the conditions of the development of experimental hypergastrinemia prevents the hypertrophy of the gastric mucosa and decreases debit of the basal gastric acid secretion in rats.